Nutritive value, antimicrobial and antioxidant activities of tchihatchewia isatidea boiss - Kırbag, Sevda; Bircan, Mürşide Gizem; Bircan, Burak (My University, 2022)
Tchihatchewia isatidea Boiss (Brassicaceae) is popularly known as “Paint and Bridal Flower”. Flower pieces and extracts can be used for painting, wound healing, and cough treatments. In this study, the nutritional and medicinal properties of T. isidea were determined. For this purpose, carbohydrate, crude oil, crude protein, crude cellulose, energy, crude ash, dry matter, moisture, element, vitamin, antioxidant capacity, DNA protective, and antimicrobial effects of T. isatidea were investigated. Crude ash, crude protein, crude fat, crude cellulose, carbohydrate, dry matter, energy, organic matter, K, Ca, Na, Fe, Cu, Zn, Pb, Mn, vitamin E and vitamin A paremeters of T. Isatidea were 14.37%, 20.60%, 1.82%, 29.02%, 63.21%, 91.57%, 351.62 kcal 72.20%, 42.5 mg/kg, 102.4 mg/kg, 260 mg/kg, 1.59 mg/kg, 0.121 mg/kg, 1.160 mg/kg, 2.16 mg/kg, 7.49 mg/kg, 22.95 mg/g and 2.82 mg/g, respectively. The DPPH (?, ?-Diphenyl-1-picrylhydrazyl) radical scavenging activity of the plant extract was ’82.34% at 100 µL, 68.20% at 50 µL, 30.80% at 25 µL and 11.68% at 10 µL’. The total oxidant level was 69.96 ?mol/L, the total antioxidant level of T. isatidea was 3.91 ?mol/L and 133.56 nmol/g Malondialdehyde (MDA). In the existence of UV and H2O2, it was found that the T. isatidea plant extract protects scDNA. It has also been established that the flower extract of the plant hinders the growth of pathogenic microorganisms at varying rates. Because of its thorny structure, the plant which can not be used as a vegetable can be transformed into a dried powdered form of powder and can be consumed with water in the form of a decoction or infusion. The plant can be mixed with powdered petroleum jelly and used as an external wound healing agent.
Keywords: Antioxidant activity; antimicrobial activity; T. isatidea; paint flower; nutritional content